Competition Assessment on Various Intercropping Patterns of Bitter Melon (Momordica charantia L) and Tomato (Solanum lycopersicum L): Competition Assessment on Various Intercropping Patterns of Bitter Melon and Tomato - Blessya, Christabel Putik; Karyawati, Anna Satyana (Journal of Tropical Life Science, 2023)
Intercropping is the practice of growing two or more crops in close proximity. Intercropping is useful for obtaining land efficiency, nutrient efficiency, and increasing biodiversity, which is in line with controlling plant-disturbing organisms. Intercropping can also be done in the rice fields, and it is hoped that the optimization of the use of the rice fields will have a good impact on rice and other crops. The adverse effect that is feared to arise due to the intercropping method is the contamination of substances through horizontal transfer of substances between plants. This study was conducted to determine the effect of competition on bitter melon and tomato intercropping. The study started from January to May 2022 in Sukorejo Village, Gondanglegi District, Malang Regency. The research stages include planting and maintaining commodities, observing growth, and organoleptic testing. The study used a Randomized Block Design (RBD) which was arranged in a non-factorial. The total treatment was 5 treatments which were repeated 4 times. The results of the research on the competitiveness of tomatoes were superior to bitter melon in a 2-line and 3-row intercropping system. From an economic point of view, intercropping in a 1:1 or 1:2 ratio is feasible because it has an R/C Ratio of more than 1. Bitter melon and tomatoes grown in polyculture with a 3-row alternate cropping pattern in a 1:2 ratio of tomatoes and bitter melon are feasible because has an R/C Ratio of 3.57 and has a more stable price for bitter melon.